Exploring the employment readiness and return to work status of breast cancer patients and related factors - Wenmin Hou; Qiaoping Li; Xiangyu Liu; Yingchun Zeng; Andy SK. Cheng (Elsevier, 2021)
Objective: To investigate the employment status, employment readiness, and other factors affecting the ease or difficulty with which breast cancer patients effect their return to work (RTW). Methods: This study adopted a mixed-method design, recruiting participants from among breast cancer patients in a cancer hospital in Hunan from December 2018 to June 2019. We approached 300 individuals, 192 of whom ultimately participated in this study. The quantitative part of the study involved several scales: the Patient Health Questionnaire-9 (PHQ-9), the Brief Fatigue Inventory (BFI), the Work Ability Index (WAI), and the Lam Assessment of Employment Readiness (LASER). The qualitative part involved a set of open-ended questions and written responses collected from 41 participants who had already returned to work at the time of data collection. Their written responses mainly concerned factors influencing RTW. Results: Forty-one breast cancer patients had returned to work. The results reported a median total Cognitive Symptom Checklist score of 9.00 (6.00, 15.25), a median WAI score of 5.00 (3.50, 9.75), a median BFI score of 26.00 (14.75, 42.00), a median total PHQ-9 score of 8.00 (5.25, 17.00), and a LASER score of 50.35 ± 11.90. Multiple regression analysis showed that the participants' cancer stage, cognitive limitations, depression, fatigue, and work ability were significant predictors of employment readiness (P < 0.05). Exploring the qualitative data, we found that higher skill levels, better social support, and a flexible work schedule facilitated RTW; stress, lack of confidence in one's work skills, depression, and fatigue are all possible barriers to RTW. Conclusion: The findings indicate that breast cancer patients have a low level of employment readiness. Nurses and other healthcare providers can develop relevant interventions to promote employment readiness and ultimately achieve RTW in this study population.